Pengelolaan Penyakit Kuning pada Tanaman Lada oleh Petani di Wilayah Bangka - Abdul Munif; Ita Sulistiawati (Jurnal Fitopatologi Indonesia, 2014)
Yellow disease caused by plant-parasitic nematodes are still a major problem on pepper production area in Bangka region. Significant yield losses occurred due to yellow disease. The objective of this research was to survey the yellow disease incidence and to study farmer’s knowledge, attitude and practices on the management of yellow disease of black pepper in Bangka district, Central Bangka and South Bangka. This study consisted of a survey of the incidence of yellow disease in the field and interviews to the farmers. The result showed that the yellow disease had infected nearly all of black pepper fields in the areas with incidence of as much as 20–60%. Almost all of the respondents reported that the yellow disease was the major disease of black pepper in Bangka region. Farmers’ level of knowledge about the causal of disease, symptoms, ecology and control methods of the yellow disease are still very limited. Various control measures have been done by farmers to combat the disease, especially by removing and burning the infected plants or by application of lime. A few farmers did not even controlling the disease. Pesticides have been used by a few farmers to control the yellow disease, but the application of pesticide does not in line with integrated pest management principles.